The Impact of Creative Industries on Economic Growth: Case Studies in Developing Countries in Malaysia and Indonesia - Muhammad Syafri; Mochammad Syafiuddin Shobirin; Dhiana Ekowati; Nuril Maghfirah (West Science Journal Economic and Entrepreneurship, 2023)
This research presents a comprehensive examination of the impact of the creative industry on economic growth in the developing nations of Malaysia and Indonesia. Utilizing a mixed-methods approach, combining quantitative analyses and qualitative insights, the study explores the intricate relationships between creative industry performance, government policies, and cultural dynamics. Quantitative results reveal a statistically significant positive correlation between the creative industry and economic growth in both countries, with variations observed in export earnings and innovation. Government policies were found to significantly influence the creative sector's contribution to GDP. Qualitative findings underscore the pivotal role of cultural dynamics in shaping creative outputs and highlight challenges and opportunities within the industry. The synthesis of these results offers valuable insights for policymakers, economists, and stakeholders seeking to harness the economic potential of the creative industry for sustainable development in diverse socio-cultural contexts.